United Kingdom : Financial Sector Assessment Program-Review of the Bank of England's Liquidity Provision Framework-Technical Note. (IMF Staff Country Reports; Country Report ;, 2016)
This paper provides a review of the liquidity provision framework and recent developments in the United Kingdom. The Bank of England's (BoE's) Sterling Monetary Framework is the mechanism used in the United Kingdom to direct liquidity provision. The BoE's relatively wide-ranging and accessible liquidity insurance framework raises three key questions and four other issues relevant to financial stability. The quantification of implications of the liquidity framework for the BoE balance sheet is still a work in progress. Safeguards are generally sufficient, although the BoE should ensure that lower level of supervisory scrutiny directed at small- and medium-sized enterprises does not adversely impact its horizon-scanning for firms at risk of requiring liquidity support.